2020
DOI: 10.1101/2020.06.05.20107011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A COVID-19 outbreak in a rheumatology department upon the early days of the pandemic

Abstract: Objectives: To describe our experience with a coronavirus disease 2019 (COVID-19) outbreak within a large rheumatology department, early in the pandemic. Methods: Symptomatic and asymptomatic healthcare workers (HCWs) had a naso-oropharyngeal swab for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and were followed clinically. Reverse transcription polymerase-chain reaction (RT-PCR) was repeated to document cure, and serological response was assessed. Patients with risk contacts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Overall, 22 unique cohorts of participants described in 24 studies (15 cohorts, 7 cross sectional) reported the proportion of asymptomatic infection at initial testing and/or the proportion of COVID-19 infections remaining asymptomatic throughout follow-up; study characteristics are summarized in Table 1 . Study cohorts were from the USA (n = 10) [ 6 , 9 , 60 62 , 66 , 69 , 73 , 75 , 78 , 80 , 81 ], Europe (n = 8) [ 63 , 67 , 68 , 70 , 72 , 74 , 76 , 77 ], and Asia (n = 4) [ 65 , 70 , 79 , 84 ]. Definition of asymptomatic infection was variable among studies, ranging from absence of symptoms in the previous 14 days to only absence of symptoms at time of testing.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 22 unique cohorts of participants described in 24 studies (15 cohorts, 7 cross sectional) reported the proportion of asymptomatic infection at initial testing and/or the proportion of COVID-19 infections remaining asymptomatic throughout follow-up; study characteristics are summarized in Table 1 . Study cohorts were from the USA (n = 10) [ 6 , 9 , 60 62 , 66 , 69 , 73 , 75 , 78 , 80 , 81 ], Europe (n = 8) [ 63 , 67 , 68 , 70 , 72 , 74 , 76 , 77 ], and Asia (n = 4) [ 65 , 70 , 79 , 84 ]. Definition of asymptomatic infection was variable among studies, ranging from absence of symptoms in the previous 14 days to only absence of symptoms at time of testing.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the change in eligible study designs, this update excludes 66 articles from earlier versions, comprising 23 contact tracing studies or outbreak investigations, 39 screening studies, and four mathematical models (S1 Table). This review version included a total of 107 studies addressing one or more objectives; 94 empirical studies that estimate the proportion of people with asymptomatic SARS-CoV-2 (summarised in Table 1 and S2 Table) [39-48, 50-54, 56-80, 82-90, 92-97, 99-102, 104-138], five studies reporting on secondary attack rates [119, 129, 138140], and 11 mathematical modelling studies reporting on the contribution of asymptomatic or presymptomatic infection to all SARS-CoV-2 transmission [7, 49, 55, 81, 91, 98, 103, 141144].…”
Section: Resultsmentioning
confidence: 99%
“…The 94 studies reported on 16,193 people with SARS-CoV-2 infection (5,905 defined as having asymptomatic infection) in 31 countries [39-48, 50-54, 56-80, 82-90, 92-97, 99-102, 104-138] (Table 1). Thirty-two studies, including 9,121 infected people, were done in the United States (S3 Table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations